Analysis of the influence of the use of Anglicism in customers of the stores at Quicentro Shopping - Bertone García, Andrea Margarita (2008)
The theme of this thesis is: Analysis of the influence of the use of Anglicisms in Customers of the stores at Quicentro Shopping. The research has been done in Quito, at Quicentro Shopping, and it has been applied to people of different ages. The methodologies applied are scientific, analytic and descriptive; the techniques used through this research were, note-taking, Internet research, direct observation, photos, interviews, focus groups and surveys. The instruments used here were, direct observation forms, questionnaires. The fundamental criterion is to give an answer or solution to a current problem: the loose of identity of our culture when using Anglicism through advertising. The results obtained from this research are various. At the end the reader of this work will find out which is the effect that the use of Anglicism has in our society.